The Return of Death in Times of Uncertainty—A Sketchy Diagnosis of Death in the Contemporary ‘Corona Crisis’ - Michael Hviid Jacobsen; Anders Petersen (Social Sciences, 2020)
For most parts of human history, death was an integral part of life, something that prehistoric and premodern man had no other option than to live with as best as possible. According to historians, death was familiar and tamed, it was at the center of social and cultural life. With the coming of modern secular society, death was increasingly sequestrated and tabooed, moved to the outskirts of society, made invisible and forbidden. Death became a stranger, and the prevalent attitude towards death was that of alienation. At the threshold of the 21st century, the topic of death again began to attract attention, becoming part of a revived death attitude described as ‘Spectacular Death’. In the article, the authors diagnose, analyze, and discuss the impact of the return of death during the current ‘Corona Crisis’, arguing that despite the fact that the concern with death is at the very core of the management of the crisis, death as such remains largely invisible. In order to provide such a diagnosis of the times, the authors initially revisit the prevailing death attitudes in the Western world from the Middle Ages to the present day.